2003
DOI: 10.1073/pnas.252774999
|View full text |Cite
|
Sign up to set email alerts
|

Tadpole skin dies autonomously in response to thyroid hormone at metamorphosis

Abstract: Transgenic tadpoles that express a dominant negative thyroid hormone (TH) receptor specifically in their skin undergo normal metamorphosis, with one exception: they retain a larval epidermis over the developing adult epithelium. TH-induced death of the tadpole epidermis is inhibited by the dominant negative TH receptor whereas the TH-induced response of the neighboring fibroblasts and the cells that form the adult skin occur normally. Therefore death of the tadpole skin is a direct and cell autonomous target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…In the skin, the outer two-cell layers of the epidermis died by apoptosis during the climax [59], showing the presence of caspase-3 [83]. At metamorphosis, number of larval red blood cells decreased whereas adult ones increased.…”
Section: Several Aspects Of Apoptosis At Metamorphosismentioning
confidence: 99%
“…In the skin, the outer two-cell layers of the epidermis died by apoptosis during the climax [59], showing the presence of caspase-3 [83]. At metamorphosis, number of larval red blood cells decreased whereas adult ones increased.…”
Section: Several Aspects Of Apoptosis At Metamorphosismentioning
confidence: 99%
“…cells releasing proteins that kill neighboring cells) was not involved. The suicide model is also supported by the observation that tadpole skin cells died autonomously in response to TH during the metamorphosis climax (25).…”
Section: Murder Model and Suicide Modelmentioning
confidence: 78%
“…All melanocytes disappeared within 2 months. Similarly, TH treatment causes autonomous death in a tailderived myoblastic cell line and larval epidermal cells (24,25), implying that larval skin cells undergo apoptosis in response to endogenous TH produced by recipient frogs. If this hypothesis is correct, larval skin grafts should survive longer with the addition of a TH synthesis inhibitor (methimazole) into breeding water.…”
Section: Ouro Proteins Are Not Necessary For Tail Resorption In X Trmentioning
confidence: 99%
“…In Xenopus tadpole, transcript levels of different caspases increase in the regressing tail and remodeling intestine during metamorphosis, supporting a role for caspases in metamorphic cell death (Yaoita and Nakajima, 1997;Nakajima et al, 2000;Rowe et al, 2002;. The activation of caspases-3, -6, -7, and -9 is observed in apoptotic tailderived cells, regressing tail and remodeling dorsal skin (Nakajima et al, 2000;Rowe et al, 2002Rowe et al, , 2005Das, 2002;Schreiber and Brown, 2003;Nakajima and Yaoita, 2003). Moreover, Caspase-3 inhibitors have been shown to impede TH-induced apoptosis of a myoblastic cell line derived from tadpole tail and intestinal cells (Su et al, 1997;Yaoita and Nakajima, 1997).…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies have indeed confirmed the crucial role of TH and shown that TH is directly responsible for different cell autonomous and tissue-specific cell destruction programs (Berry et al, 1998;Elinson et al, 1999;Huang at al., 1999;Huang and Brown, 2000;Schreiber and Brown, 2003). Although some studies have investigated the possible role of adult-type spleno-cytes to induce apoptosis in larval tail cells by means of an immunological recognition mechanism (Izutsu and Yoshizato, 1993;Izutsu et al, 1996), others have focused on the role of proteinases involved in apoptosis of larval intestinal epithelium and tissue remodeling (Ishizuya-Oka et al, 2000).…”
Section: Introductionmentioning
confidence: 99%